Metacognitive Awareness, Monitoring of Comprehension, Metacognitive Training - Bushra Ahmed Khurram (JSSH, 2023)
The aim of this paper is to provide a review and synthesis of the literature on metacognition and reading in children. The paper begins with a brief discussion of what metacognition is and presents the components of metacognition. It then reviews the key studies that have been conducted on metacognition and reading in children. The first part of the review discusses the empirical studies which examine children’s metacognitive knowledge. The second part considers the research concerned with children’s monitoring of comprehension.